Evaluation of various confirmatory tests for the diagnosis of aldosterone-producing adenoma. (May 2020) - Kidoguchi, Satoshi; Sugano, Naoki; Kawauchi, Ruri; Nakashima, Daisuke; Hayashi-Ishikawa, Naomi; Tokudome, Goro; Yokoo, Takashi
Introduction: Adrenal venous sampling is useful for discriminating unilateral and bilateral hypersecretion in patients with primary aldosteronism, but it is relatively invasive. To determine the site of hypersecretion more non-invasively, we evaluated predictors of unilateral hypersecretion. Materials and methods: We evaluated the baseline characteristics and the results of confirmatory tests of 123 patients with primary aldosteronism who underwent adrenal venous sampling. Results: Unilateral hypersecretion was identified in 22.0%. The plasma aldosterone concentration and aldosterone–renin ratio were significantly higher and serum potassium concentration and plasma renin activity were significantly lower in patients with unilateral hypersecretion. Plasma aldosterone concentrations after captopril challenge test, saline infusion test and rapid adrenocorticotropic hormone stimulation test were significantly higher among patients with unilateral hypersecretion. The plasma aldosterone concentration reduction ratio in saline infusion test and plasma aldosterone concentration elevation ratio during rapid adrenocorticotropic hormone stimulation test were significantly higher in patients with unilateral hypersecretion. However, areas under the curve for these parameters were not superior to the values after confirmatory tests. Conclusions: The plasma aldosterone concentration values after captopril challenge test, saline infusion test and rapid adrenocorticotropic hormone stimulation test were useful for identifying patients with unilateral hypersecretion. However, value changes or ratios during confirmatory tests are less useful for this aim.